Evaluating The Performance Of Multimedia Learning Systems Over Traditional System Of Learning - Majed Mustafa Suliman Oun Alla
Recent advances in multimedia technology have spurred the development of E-learning methods as an alternative to long-dominated traditional learning system. There is a lack of extended research to address issues regarding the quality factors of how to develop a model to support multimedia learning system. Traditional learning system has limited use of technology and it is not compatible with multimedia learning system which is presently used to deliver learning content globally. However, to develop a cost-effective learning system requires thorough evaluation of multimedia and traditional system of learning. Exploring multimedia learning system and traditional system of learning based on information and system quality factors in the present study stands out to support learning approaches in universities. To achieve this, both quantitative and qualitative approaches were used for data collection and data analysis. Data were collected by using questionnaire and were validated by using interviews from the Department of Computer Science at the National University of Malaysia (UKM) as a case study for this research. Quantitative data was collected from 243 undergraduate students and qualitative in-depth interview was conducted among 5 experienced e-learning lecturers. Quantitative data was statistically analyzed using Special Package for the Social Science (SPSS) and Analysis of Moment and Structure (AMOS) software. Reliability statistics based on Cronbach's alpha value at .70 showed that all the research items were consistent and reliable. The result was further subjected to Exploratory Factor Analysis (EFA) to structurally represent the dimensions of the research variables. Good model fit indices were achieved using standardized measurement criteria. Standardized regression weight value for all paths were more than 0.200and this implied that the model gave better description of the relationships among the research items and the result was evaluated using standardized residual covariance matrix for one-dimensional model analysis. A full model for learning system with a standardized solution indicated goodness of fit RMSEA= 0.042, GFI = 0.905. NFI= 0.933, TLI= 0.927 and CFI = 0.940 respectively. Path analysis for all the research hypothesis statement shows that the assumptions were accepted. Findings showed that information quality and system quality dimensions are influencing the performance of multimedia learning system and traditional system of learning. Findings showed that traditional learning system enhanced by multimedia system of learning. Thus, implementation of the present research findings could transform learning especially in the higher education.